Pengaruh Promosi Melalui Media Sosial Instagram dan Online Customer Review di Aplikasi Pesan Antar Makanan Terhadap Minat Beli Konsumen UMKM Eloka Corndog Kota Jambi - Chinta Yurike Utomo; Efni Anita; Nurrahma Sari Putri (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2024)
This research aims to determine and analyze the influence of the independent variable on the dependent variable. The method used in this research is a quantitative method. The sample in this study was 100 active Instagram users around the MSME Eloka Corndog, Jambi City. The research results show that social media (X1) has a significant effect on consumer buying interest (Y) with a Tcount value of 3.176>Ttable 1.984 and a Sig value of 0.002<0.05, which means Ho is rejected and Ha is accepted. Online Customer Review (X2) shows that there is a significant influence on Consumer Purchase Interest (Y). with a calculated T value for the Online Customer Review variable of 7,736>1.984 with a significance value of 0.001<0.05. So it can be concluded that Ho is rejected and Ha is accepted. Simultaneously (X1), (X2) and (X3) simultaneously influence (Y) by 0.000<0.005 and the value of Fcount > Ftable 163,368>3.10.